Learner-Friendly Kanji Learning System with Radical Analysis - Jungpil SHIN; Yusuke Shimizu (Institute of Advanced Engineering and Science, 2012)
This paper presents a novel friendly Kanji learning system using Radical Analysis to enable foreign people and elementary school students to learn Kanji by an interesting and efficient way. This way is for characters to analyze for each radical, to divide into some parts, and to correct strokes for each divided part. Here, the Radical Analysis Database (RAD) is used for dividing characters. RAD is a database to analyze characters for each radical and divide into some parts. On the other hand, characters are corrected by using a threshold. The threshold is a judgment value in the correction and learners can set it freely by handling threshold bars put on the interface. Then, the novel system is improved so that learners can set thresholds for each divided part. Since each bar corresponds to each part, the system judges whether each part is corrected or not according to set thresholds. Hence, since learners can freely determine radicals or parts in which they want to be instructed intensively, they can practice only their radicals not good or part of the character and easily master difficult characters, too. In addition, an animation helps learners understand the order of strokes virtually. Since each stroke used in this animation is displayed with different colors, learners can also understand virtually where the same strokes are from and to at once.DOI: http://dx.doi.org/10.11591/ijere.v1i1.479